PENGARUH PERBEDAAN JENIS UMPAN TERHADAP HASIL TANGKAPAN SIDAT (Anguilla sp) DI SUNGAI SIKUCING, KABUPATEN PURWOREJO - Wazir Mawardi; Anggraini Cahyaningtias; Julia Eka Astarini; Fis Purwangka (Jurnal Teknologi Perikanan dan Kelautan, 2021)
One of the economically valuable fish in the Sikucing River is an eel. Sikucing River is an upstream river located in Purworejo Regency, Central Java. The eel in Sikucing River is usually captured using a handline with diverse baits. The research aims to determine the type of bait favored by the eel. The baits used in this research were worms, shrimp, golden snails, and coconut caterpillars. The research uses four types of bait because the availability of these baits is still a lot and affordable. The research was conducted for 36 days and in one day there were two bait installments (namely the afternoon and evening). Bait installments were carried out at eight locations along the Sikucing River. Based on the research there are five types of fish caught on handline, namely eels, carps, snakehead fishs, lempon fishs, and turtles. The dominant catch from this research was eel with 40 individuals (or 30,173 kg). The eels were caught on all four types of bait, but the highest catch was obtained from the type of coconut caterpillar bait. Shrimp and snail were a type of bait that has the lowest eel catch (as many as 3 individuals).